PENGARUH PENYULUHAN DENGAN MEDIA WHATSAPP GROUP TERHADAP PENGETAHUAN DAN SIKAP TENTANG MAKANAN CEPAT SAJI - Luh Gde Ary Widayani; Anak Agung Gde Raka Kayanaya; I Ketut Kencana (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2021)
Currently there is a shift in eating patterns whose composition in the community contains high fat, cholesterol, but low in fiber, namely fast food. Various impacts on health arise because a person consumes fast food, so that efforts are needed to limit fast food intake with nutritional education to increase the knowledge and attitudes in choosing food. Nutritional education is done through the WhatsApp group application by considering the number of users and facilitating access to information. This study aims to knowing the effect of nutritional education with whatsapp groups on knowledge and attitudes about fast food. This type of research is a pre-experimental study with one-group pretest-posttest design applied to 33 respondents using purposive sampling. This research was conducted at SMA Negeri 8 Denpasar in March 2020. Data collection instruments used a questionnaire of knowledge and attitudes about fast food. The results showed that knowledge before nutritional education was the average score is 71.40 and after nutrition education the average score is 78.13. Attitudes before nutrition education was the average score is 72.02 and after nutrition education the average score is 77.93. From the results of the paired sample t-test, it is known that there is a significant difference between knowledge and attitudes about fast food before and after nutritional education with WhatsApp Group media.Keywords: Fast food, Whatsapp, Nutritional education.